(untitled) (Research, Society and Development, 2019)
It is necessary to provide quality services/products, being an essential factor for any company to remain in the market, so it is necessary to create strategies, seek innovations, adaptations and improvements, to meet the needs and expectations of customers, thus obtaining satisfactory results. This research aims to verify the level of quality of services offered by the University Paulista-UNIP in the city of Itaporanga-PB, in the perception of students of higher education in Administration, Physical Education and Social Work. In this paper will be presented concepts about quality in services, quality in educational services and the importance of distance higher education, these topics addressed theories that contributed to the contextualization of the theme. Regarding the methodological process, an exploratory, qualitative and quantitative research and a case study were conducted from an online questionnaire. Through the results found, it was possible to identify failures and successes in relation to the services provided, being noticeable relevant aspects that demonstrated the satisfaction of the interviewees, was also identified some factors that showed failures according to the students’ perception, however, these points need to be improved to meet student needs. From the information obtained, it was possible to conclude that Universidade Paulista offers quality services, since it has been demonstrated students satisfaction with the services.